2010
DOI: 10.1142/s0219887810004622
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling for Dirac Fermions in Constant Magnetic Field

Abstract: The tunneling effect of two-dimensional Dirac fermions in a constant magnetic field is studied. This can be done by using the continuity equation at some points to determine the corresponding reflexion and transmission coefficients. For this, we consider a system made of graphene as superposition of two different regions where the second is characterized by an energy gap t'. In fact, we treat concrete systems to practically give two illustrations: barrier and diode. For each case, we discuss the transmission i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 13 publications
3
14
0
4
Order By: Relevance
“…Note that, for B = B ′ we discover the results obtained in [19], which shows that our results are more generals.…”
Section: Reflexion and Transmission Coefficients In The Presence Of T ′supporting
confidence: 78%
See 1 more Smart Citation
“…Note that, for B = B ′ we discover the results obtained in [19], which shows that our results are more generals.…”
Section: Reflexion and Transmission Coefficients In The Presence Of T ′supporting
confidence: 78%
“…Subsequently, The tunneling effect of two-dimensional Dirac fermions in a constant magnetic field is studied [19]. This is done by using the continuity equation at fixed points to determine the corresponding reflexion and transmission coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that contrary to the tunneling through a potential barrier, the transmission of electrons was, in this case, smaller than the one for normal incidence. These results were extended to the case of a magnetic field case [15] and different generalizations were obtained.…”
Section: Introductionmentioning
confidence: 94%
“…Motivated by the above reasons and in particular the investigation made in [14] and [15], we would like to extend the study of tunneling phenomena through a graphene sheet deposited on SiO 2 -BN layer in the presence of an external magnetic field B and double barrier potentials. Note that, actually there were many theoretical investigations on tunneling of electrons in graphene in the presence of magnetic field e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Fenomena fisika akan lebih menarik apabila partikel bergerak dalam suatu sistem yang dipengaruhi medan atau dalam kondisi yang lebih kompleks, semisal sistem beberapa partikel dimana ada interaksi antar partikel dan sistem yang mendapat pengaruh medan elektromagnet eksternal [16,17,18]. Sejauh ini, penelitian-penelitian yang ada masih membahas satu partikel baik fermion maupun boson berada dalam sistem potensial penghalang yang bergerak secara periodik tanpa ada pengaruh apapun.…”
unclassified